Functional additives for solid polymer electrolytes in flexible and high‐energy‐density solid‐state lithium‐ion batteries. Issue 6 (15th September 2021) - Chen, Hao; Zheng, Mengting; Qian, Shangshu; Ling, Han Yeu; Wu, Zhenzhen; Liu, Xianhu; Yan, Cheng; Zhang, Shanqing
Abstract: Solid polymer electrolytes (SPEs) have become increasingly attractive in solid‐state lithium‐ion batteries (SSLIBs) in recent years because of their inherent properties of flexibility, processability, and interfacial compatibility. However, the commercialization of SPEs remains challenging for flexible and high‐energy‐density LIBs. The incorporation of functional additives into SPEs could significantly improve the electrochemical and mechanical properties of SPEs and has created some historical milestones in boosting the development of SPEs. In this study, we review the roles of additives in SPEs, highlighting the working mechanisms and functionalities of the additives. The additives could afford significant advantages in boosting ionic conductivity, increasing ion transference number, improving high‐voltage stability, enhancing mechanical strength, inhibiting lithium dendrite, and reducing flammability. Moreover, the application of functional additives in high‐voltage cathodes, lithium–sulfur batteries, and flexible lithium‐ion batteries is summarized. Finally, future research perspectives are proposed to overcome the unresolved technical hurdles and critical issues in additives of SPEs, such as facile fabrication process, interfacial compatibility, investigation of the working mechanism, and special functionalities. Abstract : Functional additives could afford significant advantages in high‐voltage lithium‐ion batteries, lithium–sulfur batteries, and flexible lithium‐ion batteries by boosting ionic conductivity, increasing the ion transference number, improving high‐voltage stability, enhancing mechanical strength, inhibiting lithium dendrite, and reducing flammability.